An extraordinary new hyla from colombia (1943)
My friend and colleague Hermano Nicéforo-María of the Instituto de La Salle in Bogotá very kindly allowed me to examine some specimens he recently received from Hermano Daniel, Director of the Museo of the Colegio San José in Medellin, among which was a single male of a tree-frog so extraordinary that I could scarcely believe my eyes (and I am a long-time "aficionado" of tree-frogs). It is unquetionable new to science, and may appropriately be called.